Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/21655979.2021.1997078
|View full text |Cite
|
Sign up to set email alerts
|

PIWI interacting RNAs perspectives: a new avenues in future cancer investigations

Abstract: As a currently identified small non-coding RNAs (ncRNAs) category, the PIWI-interacting RNAs (piRNAs) are crucial mediators of cell biology. The human genome comprises over 30.000 piRNA genes. Although considered a new field in cancer research, the piRNA pathway is shown by the existing evidence as an active pathway in a variety of different types of cancers with critical impacts on main aspects of cancer progression. Among the regulatory molecules that contribute to maintaining the dynamics of cancer cells, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 201 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…piRNAs are small non-coding RNA molecules consisting of 23-31 nucleotides and are mainly involved in the regulation of gene expression and maintenance of genomic integrity. Many studies have shown that piRNAs differ from miRNAs or siRNAs in terms of their chemical structure, size, processing, precursors, associated proteins, and functional mechanisms [2]. piRNAs have 2'-O-methylation at their 3'-end and bind to a PIWI protein, an Argonaute/PIWI family protein, to form the piRNA-induced silencing complex (piRISC).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…piRNAs are small non-coding RNA molecules consisting of 23-31 nucleotides and are mainly involved in the regulation of gene expression and maintenance of genomic integrity. Many studies have shown that piRNAs differ from miRNAs or siRNAs in terms of their chemical structure, size, processing, precursors, associated proteins, and functional mechanisms [2]. piRNAs have 2'-O-methylation at their 3'-end and bind to a PIWI protein, an Argonaute/PIWI family protein, to form the piRNA-induced silencing complex (piRISC).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The gene regulatory functions of piRNAs in a wide range of contexts, including signal transduction and tumour suppressor pathways, have been described [95,96]. The potential efficacy of piRNAs and Piwi proteins as diagnostic/prognostic markers and novel therapeutic agents has also been extensively described [97][98][99][100][101].…”
Section: Piwi-interacting Rnas (Pirnas)mentioning
confidence: 99%
“…Key roles of PiwiRNAs in oncology include: Tumor initiation and progression : PiwiRNAs exhibit abnormal expression patterns in various cancer types. Piwi proteins, such as PIWIL1 and PIWIL2, are upregulated in cancer cells and have been associated with enhanced tumor growth, invasion, metastasis, cancer stemness, epithelial-mesenchymal transition (EMT), and chemotherapy resistance [69] . Epigenetic regulation : PiwiRNAs are implicated in the modulation of epigenetic modifications, including DNA methylation and histone modifications.…”
Section: Piwirnas and Their Functional Implications In Cancer Develop...mentioning
confidence: 99%
“…Tumor initiation and progression : PiwiRNAs exhibit abnormal expression patterns in various cancer types. Piwi proteins, such as PIWIL1 and PIWIL2, are upregulated in cancer cells and have been associated with enhanced tumor growth, invasion, metastasis, cancer stemness, epithelial-mesenchymal transition (EMT), and chemotherapy resistance [69] .…”
Section: Piwirnas and Their Functional Implications In Cancer Develop...mentioning
confidence: 99%